Time series analysis based study of a mass-spring-like oscillation and detachment of a metal pendant droplet. (1st December 2016) - Jeromen, Andrej; Govekar, Edvard
Abstract: The subject of this study is the vertical mass-spring-like oscillation of a pendant droplet and its resonant detachment, which was experimentally observed in the process of laser droplet generation from a metal wire. The process was characterized by various time series, which were generated from a sequence of infrared intensity images of the process. Following a visual inspection of pendant droplet images and an analysis of a wavelet based time-frequency map of the droplet's vertical displacement time series, the pendant droplet's oscillation is described by a time-variable mass-spring system. Based on the characteristics of the time-frequency map, the resonant nature of the pendant droplet detachment was demonstrated. Additionally, an algebraic expression was formulated, which can be used to predict the detached droplet's diameter as a function of the laser pulse frequency. Highlights: Oscillating metal pendant droplet detachment was studied using time series analysis. A t–f map of the pendant droplet vertical displacement time series was calculated. Based on the t–f map, the pendant droplet was described as a mass-spring system. The t–f map showed the resonant nature of the pendant droplet detachment. The detached droplet diameter was predicted by an algebraic formula.